Method for testing perovskite thin film stability and perovskite thin film interface reaction

By depositing an oxide layer on the surface of the perovskite film, peeling off the influence of interface reaction and volatility, and conducting light and thermal aging tests, the problems of perovskite battery stability and interface reaction are solved, and efficient screening and reliable characteristics evaluation of stable perovskite components are achieved.

CN119881215AActive Publication Date: 2025-04-25TRINA SOLAR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510071786.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The stability of perovskite batteries is affected by the stability and interface reaction of the perovskite film itself. It is difficult for the prior art to effectively peel off the interface reaction and volatility, resulting in the inability to accurately screen out stable perovskite components.

Method used

By depositing an oxide layer on the surface of the perovskite film that does not react chemically with the perovskite structural substances, it completely covers all surfaces of the film, peel off the influence of interface reaction and volatility, and the characteristics of the perovskite structural substances are measured by aging tests such as light and heat.

Benefits of technology

This method can more accurately evaluate the stability of perovskite films, reduce the impact of interface reactions and volatility, improve the screening efficiency of stable perovskite components, and make the measured characteristics more reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881215A_ABST
    Figure CN119881215A_ABST
Patent Text Reader

Abstract

The invention belongs to the photovoltaic field, and particularly relates to a test method for perovskite film stability and perovskite film interface reaction. The method for testing the stability of the perovskite thin film comprises the step of carrying out stability characterization on the perovskite thin film of which the surface is completely coated with an oxide layer. According to the test method, the influence of interface and volatilization can be stripped, the stability of the perovskite thin film can be tested, and then the stable perovskite structure substance can be rapidly and efficiently screened out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaics, and in particular relates to a method for testing the stability of a perovskite film and the interface reaction of a perovskite film. Background Art

[0002] Organic-inorganic hybrid perovskite materials have the advantages of high absorption coefficient, adjustable bandgap, long carrier diffusion length, high defect tolerance, simple preparation process, and low material and preparation costs. They are considered to be the new materials closest to commercialization in the photovoltaic market in recent years. After only more than a decade of research, single-junction perovskite cells have achieved a high photoelectric conversion efficiency, surpassing the currently commercialized cadmium telluride and copper indium gallium selenide cells, and are very close to the mainstream crystalline silicon (26.7%) solar cells in the market. Perovskite tandem solar cells have the advantages of high efficiency and low cost, and are considered to be one of the technologies that are expected to achieve large-scale terrestrial photovoltaic applications. Perovskite tandem cells have gradually become a hot topic in the world's photovoltaic research field in recent years due to their outstanding advantages such as high efficiency, low cost, and simple preparation process.

[0003] However, the biggest problem with perovskite cells is the stability of the perovskite film itself. A large number of perovskite components will decay rapidly under the action of light and heat, resulting in a significant decrease in device performance, which seriously affects the progress of the practical application of perovskite cells. Research on stability issues will become the core issue of greatest concern to academia and industry. The core idea of ​​preparing stable perovskites is to first find photothermally stable perovskite components, and then find suitable transport layer materials and interface passivation materials for them.

[0004] At present, it is generally recognized that the stability of the perovskite material itself is the most critical limiting factor for the long-term stability of its devices. However, at present, perovskite also has the problem of reaction failure between it and the directly connected interface transmission layer. It also has the problem of degradation due to reaction with water in the air and release of organic gas due to reaction at high temperature, which leads to accelerated reaction. These problems will be significantly reduced in the perovskite device after packaging. Therefore, they are actually secondary factors in the actual research process. The most important stability research should focus on the changes in the crystal structure of perovskite under photothermal conditions.

[0005] The existing stability research methods mainly analyze the exposed surface of the perovskite film, and most studies on the bottom of the perovskite also have a transport layer. In this way, when studying the stability of the perovskite film itself, the stability will be limited by the volatilization of organic salts in the components and the reaction of the perovskite at the interface. At this time, the phenomena such as increased perovskite defects and decreased device performance cannot be judged as changes in the crystal structure of the perovskite layer itself or changes caused by interface decay. Ultimately, it is impossible to screen out the most stable perovskite component through experimental methods. In addition, perovskite batteries are significantly affected by their interfaces. Problems with different transport layer interfaces and electrode interfaces will seriously affect the final stability, and the instability of the perovskite material itself determines the upper limit of the stability of the battery device. In the actual research process, studying the stability of the perovskite material itself and the stability of the interface are two parallel stability research directions.

[0006] Therefore, it is urgent to develop a method to strip off the influence of interface and volatilization and test the stability of the perovskite film itself, so as to quickly and efficiently screen out stable perovskite structured materials. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a method for testing a perovskite film. The present invention deposits an oxide layer that does not chemically react with the perovskite structure material on the surface of the perovskite film, thereby removing the possibility of the perovskite structure material reacting with the interface. At the same time, the dense oxide layer on the top prevents the volatilization of organic components in the perovskite structure material. The measured properties of the perovskite structure material are more reliable than those of the device after actual packaging.

[0008] Specifically, the present invention provides a method for testing the stability of a perovskite film, wherein the testing method comprises characterizing the stability of a perovskite film whose surface is completely covered by an oxide layer.

[0009] In one or more embodiments, the oxide layer is selected from one or more of silicon oxide, aluminum oxide, and tin oxide.

[0010] In one or more embodiments, the oxide layer has a thickness of 1-400 nm.

[0011] In one or more embodiments, the perovskite film comprises a perovskite structure material, the chemical formula of the perovskite structure material is ABX3; A is a monovalent cation, including but not limited to one or more of cesium ions, rubidium ions, methylamine ions and formamidine ions; B is a divalent cation, including but not limited to one or more of lead ions, copper ions, zinc ions, gallium ions, tin ions and calcium ions; X is a monovalent anion, including but not limited to one or more of iodide ions, bromide ions, chloride ions, fluoride ions, thiocyanate ions and tetrafluoroborate ions.

[0012] In one or more embodiments, the thickness of the perovskite film is 100-5000 nm.

[0013] In one or more embodiments, the bottom of the perovskite thin film whose surface is completely covered by the oxide layer has a substrate, and the substrate is rough glass, flat glass, silicon wafer, mica sheet, quartz, metal foil or plastic.

[0014] In one or more embodiments, the method for preparing a perovskite film whose surface is completely covered by an oxide layer includes: first depositing an oxide layer, depositing a perovskite film on the oxide layer, and then depositing an oxide layer on the perovskite film to obtain a perovskite film whose surface is completely covered by an oxide layer.

[0015] In one or more embodiments, the oxide layer is deposited by atomic layer deposition, chemical vapor deposition, magnetron sputtering, evaporation, or reactive ion deposition.

[0016] In one or more embodiments, the deposition method of the perovskite film includes: dissolving a raw material of a perovskite structure material in a solvent to obtain a perovskite precursor solution; and coating the perovskite precursor solution on the upper surface of the oxide layer to obtain a perovskite film.

[0017] In one or more embodiments, the method for characterizing the stability of the perovskite film is X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis or Fourier infrared analysis.

[0018] The present invention provides a testing method for the interface reaction of a perovskite film, the testing method comprising: characterizing the interface reaction of a composite film whose surface is completely covered by an oxide layer, the composite film comprising a perovskite film and a first film in contact with the perovskite film, the first film being a hole transport layer, an interface layer or an electron transport layer.

[0019] The present invention also provides a method for testing the interface reaction of a perovskite film, the testing method comprising: characterizing the interface reaction of a half-covered film whose upper surface and side walls are covered by an oxide layer, the half-covered film comprising a perovskite film and a hole transport layer in contact with the perovskite film.

[0020] In one or more embodiments, the characterization method of the perovskite film interface reaction is electron microscopy analysis, transmission electron microscopy analysis, X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis, Fourier transform infrared analysis, time-of-flight-secondary ion mass spectrometry analysis or Kelvin probe-atomic force microscopy analysis.

[0021] In one or more embodiments, the hole transport layer is selected from one or more of p-type single crystal silicon, p-type polycrystalline silicon, p-type amorphous silicon and single molecule self-assembled materials; preferably, the hole transport layer is selected from [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, benzoic acid, 4-[bis(2,4-dimethoxybiphenyl-4-yl)amino]-biphenyl-4-carboxylic acid, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly(p-terephthalylidene)pyrrolidone, One or more of ethylene glycol formate, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 3-hexylthiophene polymer, poly-3,4-ethylenedioxythiophene:polystyrene sulfonate, 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9-spirobifluorene, 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanodimethyl-p-benzoquinone, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], antimony-doped tin oxide, NiOx, CuSCN, CuAlO2, V2O5, CdS and CdSe.

[0022] In one or more embodiments, the hole transport layer has a thickness of 0.1-200 nm.

[0023] In one or more embodiments, the electron transport layer is selected from n-type single crystal silicon, n-type polycrystalline silicon, n-type amorphous silicon, TiO2, SnO2, ZnO, ZrO2, Nb x O y , Gallium-doped zinc oxide, Indium zinc oxide, Fluorine-doped tin oxide, Indium tin oxide, Tungsten-doped indium oxide, BaSnO3, TiSnO x SnZnO x , C60, fullerene and one or more of fullerene derivatives.

[0024] In one or more embodiments, the thickness of the electron transport layer is 0.1-300 nm.

[0025] In one or more embodiments, the interface layer is selected from one or more of organic-inorganic hybrid two-dimensional perovskite, pure inorganic two-dimensional perovskite, phosphate and sulfate.

[0026] In one or more embodiments, the thickness of the interface layer is 0.1-300 nm.

[0027] In one or more embodiments, the interface layer is an organic-inorganic hybrid two-dimensional perovskite, and the thickness of the interface layer is 1-200 nm.

[0028] In one or more embodiments, the interface layer is a pure inorganic hybrid two-dimensional perovskite, and the thickness of the interface layer is 1-200 nm.

[0029] In one or more embodiments, the interface layer is phosphate, and the thickness of the interface layer is 1-20 nm.

[0030] In one or more embodiments, the interface layer is sulfate, and the thickness of the interface layer is 1-20 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the structure of a perovskite film with a surface-coated oxide layer in some embodiments of the present invention.

[0032] Figure 2 Schematic diagram of the structure of the perovskite film characterization object prepared in Example 1 (a), Comparative Example 1 (b) and Comparative Example 2 (c) of the present invention. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0035] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0036] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0037] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0038] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0039] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0040] The present invention provides a method for testing a perovskite film, the method comprising characterizing the stability of a perovskite film whose surface is completely coated with an oxide layer. In the present invention, a dense oxide layer that does not react with a perovskite structure material is coated on the surface of the perovskite film, the oxide layer completely covers all surfaces of the perovskite film, isolates it from the air, removes the possibility of the perovskite structure material reacting with the interface, prevents the volatilization of organic components in the perovskite structure material, and uses the perovskite film with the oxide layer coated on the surface for light, heat and other aging, and the measured characteristics of the perovskite structure material are more reliable than the device after actual packaging.

[0041] In the present invention, the perovskite film whose surface is completely covered by an oxide layer is the perovskite film characterization object.

[0042] In the present invention, the oxide layer can be one or more selected from silicon oxide, aluminum oxide and tin oxide. The present invention uses a dense oxide layer that does not react with halogen ions, amine ions and amidine ions in the perovskite material to fully encapsulate and wrap the surface and side walls of the perovskite film, which well blocks the penetration and destructive effect of water vapor and oxygen in the air on the perovskite film. At the same time, this material will not react with the halogen ions migrating in the perovskite to induce the degradation of the film. This method can be used to study the self-generated stability of the perovskite film material, including the influence of the perovskite component and the film-forming crystal quality on the stability. Further, some functional layers are introduced into the perovskite film, and then the surface and side walls of the perovskite film are fully encapsulated and wrapped using a dense inorganic oxide material, and then the photoelectric properties of the composite film are characterized, and the influence of the interface reaction on the material properties can be further analyzed.

[0043] In the present invention, the thickness of the oxide layer can be 1-400nm, such as 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm. In the present invention, controlling the thickness of the oxide layer within the above range is conducive to testing the performance of the perovskite film.

[0044] In the present invention, the oxide layers coated on the upper surface, lower surface and sidewalls of the perovskite film may be the same or different.

[0045] In the present invention, the perovskite film may include a perovskite structure material, the chemical formula of the perovskite structure material may be ABX3, A may be a monovalent cation, including but not limited to a cesium ion (Cs + ), rubidium ions (Rb + ), methylamine ion (CH3NH3 + , MA) and formamidinium ion (CH(NH2)2 + , FA) in one or more; B can be a divalent cation, including but not limited to lead ions (Pb 2+ ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ), gallium ions (Ga 2+ ), tin ions (Sn 2+ ) and calcium ions (Ca 2+ ) in one or more; X may be a monovalent anion, including but not limited to iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ), fluoride ion (F - ), thiocyanate ion (SCN - ), tetrafluoroborate ion (BF4 - ) and hexafluorophosphate ion (PF6 - )

[0046] In the present invention, the thickness of the perovskite film can be 100-5000nm, for example, 100nm, 500nm, 1000nm, 2000nm, 2500nm, 3000nm, 3500nm, 4000nm, 4500nm, 5000nm.

[0047] In the present invention, the bottom of the perovskite film whose surface is completely covered by the oxide layer may also have a substrate, and the substrate may be rough glass, flat glass, silicon wafer, mica sheet, quartz, metal foil or plastic.

[0048] In the present invention, the preparation method of the perovskite film whose surface is completely covered by the metal oxide layer comprises: firstly depositing an oxide layer, depositing a perovskite film on the oxide layer, and then depositing an oxide layer on the perovskite film to obtain a perovskite film whose surface is completely covered by the oxide layer.

[0049] In the present invention, the method for preparing a perovskite film whose surface is completely covered by a metal oxide layer further comprises: firstly depositing an oxide layer on the surface of a substrate.

[0050] In the present invention, the oxide layer may be deposited by atomic layer deposition (ALD), chemical vapor deposition (CVD), magnetron sputtering, evaporation or reactive ion deposition (RPD).

[0051] In the present invention, the deposition method of the perovskite film comprises: dissolving the raw material of the perovskite structure material in a solvent to obtain a perovskite precursor solution; and coating the perovskite precursor solution on the upper surface of the oxide layer to obtain the perovskite film.

[0052] In the present invention, the method for characterizing the stability of the perovskite film whose surface is completely covered by the metal oxide layer can be X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis or Fourier infrared analysis. In some implementation methods, the fluorescence analysis can be photoluminescence analysis (PL).

[0053] The present invention can also be used to study electron extraction kinetics or hole extraction kinetics.

[0054] The present invention also provides a testing method for the interface reaction of a perovskite film, the testing method comprising: characterizing the interface reaction of a composite film whose surface is completely covered by an oxide layer, the composite film comprising a perovskite film and a first film in contact with the perovskite film, the first film being a hole transport layer, an interface layer or an electron transport layer.

[0055] The present invention also provides a method for testing the interface reaction of a perovskite film, the testing method comprising: characterizing the interface reaction of a semi-encapsulated film whose upper surface and side walls are covered by an oxide layer, wherein the semi-encapsulated film comprises a perovskite film and a hole transport layer in contact with the perovskite film.

[0056] In the present invention, the characterization method of the interface reaction of the perovskite film can be electron microscopy analysis, transmission electron microscopy analysis, X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis, Fourier transform infrared analysis, time-of-flight-secondary ion mass spectrometry analysis or Kelvin probe-atomic force microscopy analysis.

[0057] In the present invention, the hole transport layer can be one or more selected from p-type single crystal silicon, p-type polycrystalline silicon, p-type amorphous silicon and single molecule self-assembly materials; preferably, the hole transport layer can be selected from [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), benzoic acid, 4-[bis(2,4-dimethoxybiphenyl-4-yl)amino]-biphenyl-4-carboxylic acid [MC-43], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Sprio-OMeTAD), polyethylene terephthalate (PET), Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), polymer of 3-hexylthiophene (P3HT), poly(3,4-ethylenedioxythiophene) (PEDOT): polystyrene sulfonate (PSS), 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9-spirobifluorene (Spiro-TTB), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanodimethyl-p-benzoquinone (F6TCNNQ), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC), antimony-doped tin oxide (ATO), NiOx, CuSCN, CuAlO2, V2O5, CdS and CdSe. One or more. In the present invention, the thickness of the hole transport layer can be 0.1-200 nm, for example, 0.5 nm, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 50 nm, 100 nm, 150 nm, 200 nm.

[0058] In the present invention, the electron transport layer can be selected from n-type single crystal silicon, n-type polycrystalline silicon, n-type amorphous silicon, TiO2, SnO2, ZnO, ZrO2, Nb x O y , gallium-doped zinc oxide (GZO), indium zinc oxide (IZO), fluorine-doped tin oxide (FTO), indium tin oxide (ITO), tungsten-doped indium oxide (IWO), BaSnO3, TiSnO x SnZnO x , C60, fullerene and one or more of fullerene derivatives. In the present invention, the thickness of the electron transport layer can be 0.1-300nm, for example, 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm.

[0059] In the present invention, the interface layer can be one or more selected from organic-inorganic hybrid two-dimensional perovskite, pure inorganic two-dimensional perovskite, phosphate and sulfate. In some embodiments, the phosphate is lead phosphate; in some embodiments, the sulfate is lead sulfate.

[0060] In the present invention, the thickness of the interface layer can be 0.1-300nm, such as 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm. In some embodiments, when the interface layer is an organic-inorganic hybrid two-dimensional perovskite, the thickness of the interface layer can be 1-200nm, such as 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm. In some embodiments, when the interface layer is a pure inorganic hybrid two-dimensional perovskite, the thickness of the interface layer can be 1-200nm, such as 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm. In some embodiments, when the interface layer is phosphate, the thickness of the interface layer can be 1-20nm, such as 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm. In some embodiments, when the interface layer is sulfate, the thickness of the interface layer can be 1-20nm, such as 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) The present invention provides an oxide layer on the surface of the perovskite film, and the oxide layer completely covers all surfaces of the perovskite film, isolating it from the air, removing the possibility of the perovskite structure material reacting with the interface, and preventing the volatilization of organic components in the perovskite structure material. The perovskite film with the oxide layer on the surface is subjected to light, heat and other aging, and the measured properties of the perovskite structure material are more reliable than the actual packaged device;

[0063] (2) The present invention can quickly and efficiently screen out stable perovskite components, and is suitable for perovskite companies to develop stable perovskite components;

[0064] (3) The testing method of the present invention can be used not only in small-throughput experimental design, but also in combination with high-throughput methods for material screening and research.

[0065] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0066] Example 1

[0067] Preparation of this example Figure 2 The perovskite film characterization object shown in (a) is as follows:

[0068] (1) depositing a 20 nm thick silicon dioxide film on a cleaned ITO glass substrate using CVD to obtain an oxide layer;

[0069] (2) coating the upper surface of the oxide layer with a perovskite precursor solution by a slit coating method to obtain a perovskite film with a thickness of 1000 nm; wherein the solute of the perovskite precursor solution is FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L;

[0070] (3) A 200 nm thick aluminum oxide layer is deposited on the upper surface and sidewalls of the perovskite film by ALD to obtain an oxide layer and a perovskite film characterization object.

[0071] Example 2

[0072] This embodiment prepares the characterization object of the interface reaction of the perovskite film, and the specific steps are as follows:

[0073] (1) depositing a 20 nm thick nickel oxide film on a cleaned ITO glass substrate by magnetron sputtering to obtain a hole transport layer;

[0074] (2) coating the upper surface of the hole transport layer with a perovskite precursor solution by a slit coating method to obtain a perovskite film with a thickness of 1000 nm; wherein the solute of the perovskite precursor solution is FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L;

[0075] (3) A 200 nm thick aluminum oxide layer is deposited on the upper surface and sidewalls of the perovskite film by ALD to obtain an oxide layer and a perovskite film characterization object.

[0076] Example 3

[0077] This embodiment prepares the characterization object of the interface reaction of the perovskite film, and the specific steps are as follows:

[0078] (1) depositing a 20 nm thick silicon dioxide film on a cleaned ITO glass substrate using CVD to obtain an oxide layer;

[0079] (2) coating the upper surface of the oxide layer with a perovskite precursor solution by a slit coating method to obtain a perovskite film with a thickness of 1000 nm; wherein the solute of the perovskite precursor solution is FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L;

[0080] (3) coating 2 mg / mL of phenylethylamine iodide (PEAI) on the surface of the perovskite film to obtain an interface layer made of organic-inorganic hybrid two-dimensional perovskite with a thickness of 2 nm;

[0081] (4) A 200 nm thick aluminum oxide layer is deposited on the upper surface of the interface layer, the interface layer, and the sidewalls of the perovskite film by ALD to obtain an oxide layer and a perovskite film characterization object.

[0082] Example 4

[0083] This embodiment prepares the characterization object of the interface reaction of the perovskite film, and the specific steps are as follows:

[0084] (1) depositing a 20 nm thick silicon dioxide film on a cleaned ITO glass substrate using CVD to obtain an oxide layer;

[0085] (2) coating the upper surface of the oxide layer with a perovskite precursor solution by a slit coating method to obtain a perovskite film with a thickness of 1000 nm; wherein the solute of the perovskite precursor solution is FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L;

[0086] (3) using a thermal evaporation method to prepare a 15 nm thick layer of C60 material on the surface of the perovskite film to obtain an electron transport layer;

[0087] (4) A 200 nm thick aluminum oxide layer is deposited on the upper surface of the electron transport layer, the electron transport layer, and the sidewalls of the perovskite film by ALD to obtain an oxide layer and a perovskite film characterization object.

[0088] Comparative Example 1

[0089] This comparative example was prepared Figure 2 (b) shows the perovskite film characterization object. The specific steps are as follows:

[0090] (1) The perovskite precursor solution was coated on the cleaned ITO glass substrate by the slit coating method to obtain a perovskite film with a thickness of 1000 nm and a perovskite film characterization object; wherein the solute of the perovskite precursor solution is FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L.

[0091] Comparative Example 2

[0092] This comparative example was prepared Figure 2 (c) shows the perovskite film characterization object. The specific steps are as follows:

[0093] (1) A perovskite precursor solution was coated on a cleaned ITO glass substrate by a slit coating method to obtain a perovskite film with a thickness of 1000 nm; wherein the solute of the perovskite precursor solution was FA 0.8 Cs 0.2 PbI3(FACs), the solvent of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the solvent volume ratio is 4:1, and the concentration of the solute in the perovskite precursor solution is 1.7 mol / L;

[0094] (2) A 200 nm thick aluminum oxide layer is deposited on the upper surface and sidewalls of the perovskite film by ALD to obtain an oxide layer and a perovskite film characterization object.

[0095] Test Example 1

[0096] The perovskite film characterization objects prepared in Examples 1-4 and Comparative Examples 1-2 were irradiated at 85° C. and AM 1.5 for 500 h, and then PL tests and XRD tests were performed. The test results are shown in Table 1.

[0097] PL test: The wavelength of the fluorescent incident light is 450nm and the intensity is 100mW / cm 2 , the detector is a CCD detector, and the detector integration time is 2000ms.

[0098] XRD test: After the test, the peak areas of the peak representing lead iodide at a 2θ angle of 12.7° and the peak representing perovskite at a 2θ angle of 14.5° were integrated, and the ratio was the ratio of lead iodide to perovskite.

[0099] Table 1: PL intensity and lead iodide / perovskite ratio of the perovskite films obtained in Example 1, Comparative Example 1 and Comparative Example 2

[0100]

[0101]

[0102] The decrease in fluorescence intensity indicates an increase in non-radiative recombination in the perovskite film, which is a direct manifestation of the decline in the photoelectric performance of the perovskite material. XRD represents the change in the physical phase. Lead iodide is the product of the decomposition of the perovskite material. The larger the ratio of lead iodide to perovskite, the more the perovskite material is decomposed.

[0103] As can be seen from Table 1, the PL intensity of the perovskite film characterization object prepared in Example 1 is greater than the PL intensity of the perovskite film characterization object prepared in Comparative Example 1 and Comparative Example 2, and the lead iodide / perovskite ratio of the perovskite film characterization object prepared in Example 1 is less than the lead iodide / perovskite ratio of the perovskite film characterization object prepared in Comparative Example 1 and Comparative Example 2, which indicates that the decomposition rate of the perovskite material in Comparative Example 1 and Comparative Example 2 is significantly faster than the decomposition rate of the perovskite material in Example 1, and the stability of the perovskite material in Example 1 is significantly higher than the stability of the perovskite material in Comparative Example 1 and Comparative Example 2, which indicates that the contact interface between the substrate and the perovskite film and the contact between the surface of the perovskite film and the external environment significantly increase the degradation rate of the perovskite material. The method for testing the stability of the perovskite film of the present invention avoids the occurrence of these situations, and the test results are more accurate.

[0104] As shown in Table 1, by comparing Example 2 with Example 1, it can be seen that the hole transport layer NiOx significantly induces the photoelectric performance of the perovskite device to decrease, and its lead iodide ratio is also higher, indicating that the decomposition of the perovskite is accelerated when the NiOx interface exists. From the results of Example 3 and Example 1, it can be seen that the organic-inorganic hybrid two-dimensional perovskite interface layer does not react with the perovskite, and the presence of this layer will not accelerate the aging and decay of the perovskite. From the comparison of Example 4 with Example 1, it can be seen that the presence of C60 will greatly accelerate the aging and decomposition of the perovskite film.

Claims

1. A method for testing the stability of a perovskite film, characterized in that: The test method involves characterizing the stability of a perovskite film whose surface is completely covered by an oxide layer.

2. The testing method according to claim 1, characterized in that: The test method has one or more of the following characteristics: The oxide layer is selected from one or more of silicon oxide, aluminum oxide and tin oxide; The thickness of the oxide layer is 1-400 nm; The perovskite film contains a perovskite structure material, and the chemical formula of the perovskite structure material is ABX3; A is a monovalent cation, including but not limited to one or more of cesium ions, rubidium ions, methylamine ions and formamidine ions; B is a divalent cation, including but not limited to one or more of lead ions, copper ions, zinc ions, gallium ions, tin ions and calcium ions; X is a monovalent anion, including but not limited to one or more of iodide ions, bromide ions, chloride ions, fluoride ions, thiocyanate ions and tetrafluoroborate ions; The thickness of the perovskite film is 100-5000nm.

3. The testing method according to claim 1, characterized in that: The bottom of the perovskite film whose surface is completely covered by the oxide layer has a substrate, and the substrate is rough glass, flat glass, silicon wafer, mica sheet, quartz, metal foil or plastic.

4. The testing method according to claim 1, characterized in that: The preparation method of a perovskite film whose surface is completely covered by an oxide layer comprises: first depositing an oxide layer, depositing a perovskite film on the oxide layer, and then depositing an oxide layer on the perovskite film to obtain a perovskite film whose surface is completely covered by an oxide layer.

5. The testing method according to claim 4, characterized in that: The oxide layer is deposited by atomic layer deposition, chemical vapor deposition, magnetron sputtering, evaporation or reactive ion deposition.

6. The testing method according to claim 4, characterized in that: The deposition method of the perovskite film includes: dissolving the raw material of the perovskite structure material in a solvent to obtain a perovskite precursor solution; coating the perovskite precursor solution on the upper surface of the oxide layer to obtain the perovskite film.

7. The testing method according to claim 1, characterized in that: The characterization method of the stability of the perovskite film is X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis or Fourier infrared analysis.

8. A method for testing the interface reaction of a perovskite film, characterized in that: The test method includes: Characterizing an interface reaction of a composite film whose surface is completely covered by an oxide layer, wherein the composite film comprises a perovskite film and a first film in contact with the perovskite film, wherein the first film is a hole transport layer, an interface layer or an electron transport layer; or The interface reaction of a half-wrapped film whose upper surface and sidewalls are covered by an oxide layer is characterized, wherein the half-wrapped film includes a perovskite film and a hole transport layer in contact with the perovskite film.

9. The testing method according to claim 8, characterized in that: The test method has one or more of the following characteristics: The characterization method of the perovskite film interface reaction is electron microscope analysis, transmission electron microscope analysis, X-ray diffraction analysis, X-ray reflection analysis, fluorescence analysis, fluorescence quantum yield analysis, optical absorption analysis, Fourier infrared analysis, time-of-flight-secondary ion mass spectrometry analysis or Kelvin probe-atomic force microscope analysis; The hole transport layer is selected from one or more of p-type single crystal silicon, p-type polycrystalline silicon, p-type amorphous silicon and single molecule self-assembly materials; preferably, the hole transport layer is selected from [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, benzoic acid, 4-[bis(2,4-dimethoxybiphenyl-4-yl)amino]-biphenyl-4-carboxylic acid, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, polyethylene terephthalate , poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], polymer of 3-hexylthiophene, poly-3,4-ethylenedioxythiophene:polystyrene sulfonate, 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9-spirobifluorene, 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanodimethyl-p-benzoquinone, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], antimony-doped tin oxide, NiOx, CuSCN, CuAlO2, V2O5, CdS and CdSe; The thickness of the hole transport layer is 0.1-200 nm; The electron transport layer is selected from n-type single crystal silicon, n-type polycrystalline silicon, n-type amorphous silicon, TiO2, SnO2, ZnO, ZrO2, Nb x O y , Gallium-doped zinc oxide, Indium zinc oxide, Fluorine-doped tin oxide, Indium tin oxide, Tungsten-doped indium oxide, BaSnO3, TiSnO x SnZnO x , C60, one or more of fullerene and fullerene derivatives; The thickness of the electron transport layer is 0.1-300 nm; The interface layer is selected from one or more of organic-inorganic hybrid two-dimensional perovskite, pure inorganic two-dimensional perovskite, phosphate and sulfate; The thickness of the interface layer is 0.1-300 nm.

10. The testing method according to claim 9, characterized in that: The interface layer is an organic-inorganic hybrid two-dimensional perovskite, and the thickness of the interface layer is 1-200 nm; or The interface layer is a pure inorganic hybrid two-dimensional perovskite, and the thickness of the interface layer is 1-200 nm; or The interface layer is phosphate, and the thickness of the interface layer is 1-20 nm; or The interface layer is sulfate, and the thickness of the interface layer is 1-20 nm.

Citation Information

Patent Citations

  • Packaging structure and packaging method of perovskite solar cell

    CN112133832A

  • Perovskite nano-enzyme as well as preparation method and application thereof

    CN118237009A

  • Method for forming surface of oxide single crystal

    JP1994183894A

  • Use of type of compounds as energy-containing material

    US20190112242A1

  • Encapsulation perovskite solar cell module and encapsulation method therefor

    WO2018219154A1